Do Weightbearing Restrictions Cause Excess Weight Gain in Children With LEGG-Calvé-Perthes Disease?. Issue 1 (12th January 2023) - Novotny, Susan A.; Hailer, Yasmin D.; Laine, Jennifer C.; Wetzel, Martha; Gillespie, Scott E.; Gilbert, Shawn R.; Goldstein, Rachel Y.; Kim, Harry K.W.; Schrader, Tim; ,
Abstract : Background: Restricted weight bearing is commonly prescribed in Legg-Calvé-Perthes Disease (LCPD), raising concerns of causing overweight or obesity. This study utilizes prospectively collected data to address the following questions: (1) does body mass index (BMI) Z-score increase over the course of LCPD follow-up; (2) is having a BMI category of normal, overweight, or obese at baseline associated with BMI Z-score changes over the course of follow-up; and (3) is the duration of weight bearing restrictions (no restrictions, <3, 3 to <6, 6 to 9, or >9 mo) associated with BMI Z-score changes. Methods: Data of 130 children aged 5 to 12 years with unilateral early-stage LCPD were extracted from an international database. Nation-specific BMI Z-scores and percentile-based weight categories were determined, and the duration of follow-up and weight bearing restrictions were calculated. Longitudinal changes in BMI Z-scores were evaluated for the 3 study questions using mixed effects linear regression models with surgery as a covariate. Sensitivity analyses were used to determine the influence of socio-cultural background (USA vs. India) for each study question. Results: During the 35.5±15.9 months of follow-up, no statistically significant increase in BMI Z-scores was observed across the entire cohort, or following stratification by baseline weight categories or the duration of the weight bearing restriction. Sensitivity analyses indicated that patients in the USA had no change in their BMI Z-score. When stratified by weight categories, the normal weight of US children had a small increase in their BMI Z-score (0.005 per mo, 95% confidence interval: 0.0002, 0.009), but this was not seen in other BMI categories. The cohort of Indian children had a small but significant decrease in their BMI Z-score (−0.005/mo, 95% CI: −0.009, −0.0002). After stratification by weight categories, a small decrease of the BMI Z-score was observed only in the Indian overweight children (−0.016 per mo, 95% CI: −0.027, −0.005) and no other BMI category. Conclusions: Weightbearing restrictions over the course of follow-up for our cohort of children with early-stage LCPD were not associated with clinically meaningful increases of BMI Z-scores. Weight gain is multi-factorial and probably not caused by weight bearing restrictions alone. Level of Evidence: III Diagnostic Study.